Tolerability-Adapted Imatinib 800 mg/d Versus 400 mg/d Versus 400 mg/d Plus Interferon-α in Newly Diagnosed Chronic Myeloid Leukemia - Hehlmann, Rüdiger; Lauseker, Michael; Jung-Munkwitz, Susanne; Leitner, Armin; Müller, Martin C.; Pletsch, Nadine; Proetel, Ulrike; Haferlach, Claudia; Schlegelberger, Brigitte; Balleisen, Leopold; Hänel, Mathias; Pfirrmann, Markus; et al. (Journal of clinical oncology, 2011)
Treatment of chronic-phase (CP) chronic myeloid leukemia (CML) with imatinib 400 mg/d can be unsatisfactory. Optimization of treatment is warranted. In all, 1,014 newly diagnosed CP-CML patients were randomly assigned to imatinib 800 mg/d (n = 338), imatinib 400 mg/d (n = 325), or imatinib 400 mg/d plus interferon alfa (IFN-α; n = 351). Dose adaptation to avoid higher-grade toxicity was recommended. First primary end point was major molecular remission (MMR) at 12 months. A higher rate of MMR at 12 months occurred with tolerability-adapted imatinib 800 mg/d than with imatinib 400 mg/d (59% [95% CI, 53% to 65%] v 44% [95% CI, 37% to 50%]; P < .001) or imatinib 400 mg/d plus IFN-α (59% v 46% [95% CI, 40% to 52%]; P = .002). Median dose in the 800-mg/d arm was 628 mg/d with a maximum dose of 737 mg/d during months 4 to 6 and a maintenance dose of 600 mg/d. All three treatment approaches were well tolerated with similar grade 3 and 4 adverse events. Independent of treatment approach, MMR at 12 months showed better progression-free survival (99% v 94%; P = .0023) and overall survival (99% v 93%; P = .0011) at 3 years when compared with > 1% on the international scale or no MMR but showed no difference in 0.1% to < 1% on the international scale, which closely correlates with complete cytogenetic remission. Treatment of early-phase CML with imatinib can be optimized. Early high-dose therapy followed by rapid adaptation to good tolerability increases the rate of MMR at 12 months. Achievement of MMR by month 12 is directly associated with improved survival.